Spatialized Pedagogy: Adapting Non-Formal Education Strategies for Stunting Prevention in Mountainous Regions - Ningsih, Yuyun Setia; Wahyudi , Adib (Future Space: Studies in Geo-Education, 2025)
Stunting is not merely a nutritional deficit but often a consequence of low spatial-health literacy in marginalized communities. This study evaluates the Family Hope Program (PKH) in Giripurno Village, Batu City, positioning it as a non-formal geographic education intervention. While the village faces high stunting rates, its mountainous topography creates distinct "spatial barriers" to educational access. Guided by Place-Based Education (PBE) theory, this research analyzes how facilitators adapt their pedagogical strategies to the rugged terrain. The method used is qualitative with a descriptive approach, utilizing purposive sampling to select key educational facilitators and beneficiaries. Data were collected through participatory observation of learning sessions, unstructured interviews, and documentation. The study reveals three key educational findings: (1) Topography creates uneven educational participation, where remote hamlets like Durek face exclusion compared to accessible ones; (2) Facilitators successfully employ Contextual Teaching and Learning (CTL) strategies, utilizing cooking demonstrations and audio-visual media as pedagogical tools to concretize abstract health concepts; and (3) The curriculum was adapted through the "Stunting School" to bridge the gap between national standards and local highland resource availability. The study concludes that successful stunting prevention requires a "Spatialized Pedagogy" that respects the physical geography of the learners.